(3QSGFd GdbGVi GdaGVds - (3YHO GdQMje Hf Ydj Hf GdSYjO GddNej, GdeYQha HGdbGVj GdaGVd,J (B596 (3g` s ((3GdHjJ GdebOS s)
(3ChdgG (B:s
(3eHJhQ Chd GdehLhO efgG(B: (3cJGH BNQ Edjg(B: (3hQO cJGH GdeLdS GdSGei dG RGd eNUhUkG HGdSdGeI hGdSdGe eaJOjkG ddfYeI hGdEfYGe s
(3BNQgG (B:s
(3cJGH Edi Gdedc GdYGOd ai GdJYRjI HGdedc GdYRjR EdG Cf Gddg SHMGfg CXgQ YWag GdNai hHefYg GdLdi GdeJjf Gdbhi HCf CHbi ajbhd ai JhOjY GdfYeI HGdedc GdYRjR dGMhd hdG bhI EdG HGddg s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B346 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B209s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B27 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs